(untitled) - Ing. Brayan Sneider Duran Bautista; MSc. Oscar Manuel Duque Suarez; Msc. July Andrea Gomez Camperos (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This research aims to develop an industrial manipulator, from its design stages to its physical creation using the embedded HMI kinematic control system, until its implementation and the selection of suitable electronic devices for its possible development. This project was designed for Tecnoacademia in Cucuta-Colombia for academic purposes, where the apprentice of this institution interacts directly with the manipulator, obtaining knowledge in robotics. Moreover, understanding the work through a graphical interface developed in the project is useful for knowing the basic concepts in robotics and the problem to be considered for understanding the work that was developed and his interface. Finally, a functional test and the teaching methodology for the apprentice are performed.